The role of biologicals in intestinal transplantation. Issue 2 (April 2016) - Pascher, Andreas; Atanasov, Georgi
Abstract : Purpose of review: This article reviews the role of biologicals in intestinal transplantation. Recent findings: Several biologicals have been used in intestinal and multivisceral transplantation for various indications, such as induction therapy, prevention and treatment of antibody-mediated rejection, desensitization, anti-inflammatory treatment, as well as treatment of Epstein–Barr virus-associated posttransplant lymphoproliferative disease. Particularly, the administration of biologicals in induction therapy such as T-cell depleting antibodies and interleukin-2 receptor antagonists have significantly contributed to the great improvement of patient and allograft outcome. Novel biologicals, such as B-cell, plasma-cell, and complement-directed agents have been successfully applied to treat antibody and complement-driven alloimmune processes to stabilize long-term outcome. Several other inflammatory allotransplant conditions have been addressed with anti-TNF-α antibodies, such as infliximab. Summary: Biologicals have contributed significantly to the recent success of intestinal transplantation. Novel developments in this field are supposed to aid in addressing various urgent needs in intestinal transplantation, such as preimmunization, antibody and complement-induced graft injury, as well as pathologies originating from innate immune responses.